Polymer–Inorganic Thermoelectric Nanomaterials: Electrical Properties, Interfacial Chemistry Engineering, and Devices - Zhang, Xiaoyan; Pan, Shuang; Song, Huanhuan; Guo, Wengai; Zhao, Shiqiang; Chen, Guang; Zhang, Qingcheng; Jin, Huile; Zhang, Lijie; Chen, Yihuang; Wang, Shun (Frontiers in Chemistry, 2021)
Though solar cells are one of the promising technologies to address the energy crisis, this technology is still far from commercialization. Thermoelectric materials offer a novel opportunity to convert energy between thermal and electrical aspects, which show the feasibility to improve the performance of solar cells via heat management and light harvesting. Polymer-inorganic thermoelectric nanocomposites consisting of inorganic nanomaterials and functional organic polymers represent one kind of advanced hybrid nanomaterials with tunable optical and electrical characteristics and fascinating interfacial and surface chemistry. During the past decades, they have attracted extensive research interest due to their diverse composition, easy synthesis, and large surface area. Such advanced nanomaterials not only inherit low thermal conductivity from polymers and high Seebeck coefficient, and high electrical conductivity from inorganic materials, but also benefit from the additional interface between each component. In this Review, we provide an overview of interfacial chemistry engineering and electrical feature of various polymer–inorganic thermoelectric hybrid nanomaterials, including synthetic methods, properties, and applications in thermoelectric devices. In addition, the prospect and challenges of polymer-inorganic nanocomposites are discussed in the field of thermoelectric energy.